Influence of Proline Utilization in Skimmed Milk Dilution of Frozen Sperm to Sperm Quality of Priangan Sheep - Waluyo, ST (ANIMAL PRODUCTION, 2006)
The objective of this research is to know the optimal concentration level of proline in the skimmed milk dilution against sperm quality of frozen sperm of Priangan sheep.  The research was done in the laboratory of artificial insemination institution, Lembang, Bandung, from November 2004 up to January 2005.  In the experiment, sperm from five of Priangan sheep collected by artificial vagina and diluted with skimmed milk, each dilution added by different dose of 10; 20; 30; 40 μg proline and without proline for control.  The experimental method used by basic with CRD continued by Duncan multiple rank test 5% significant.   Observed variable was sperm quality measured after dilution and equilibration, and after thawing including percentage of motility, live, intact plasma membrane and spermatozoa intact head acrosome.  The result of experiment show that percentage of motility and life spermatozoa after dilution were not significant after treatment (P>0.05), after equilibration and thawing resulted the highest percentage of motility and life in the treatment of P30 (72.00 and 54.00%), and (82.20 and 67.60%) significantly different compared to the other treatment (P<0.05), except with P20 not significantly different (P>0.05), after equilibration the treatment P30 had the highest percentage of plasma membrane and significantly different with the other treatment (P<0.05), except with P40 which was not significantly different (P>0.05), and percentage of intact head acrosome was significantly different compared with the other treatment (P<0.05).  Where as post thawing P30 had the highest percentage of intact plasma membrane and intact head acrosome (61.20 and 65.20) compared to the other treatment (P<0.05). (Animal Production 8(1): 22-27 (2006) Key Words : Proline, sperm, frozen, sheep